Flow pattern identification and detection in T-junction microchannels for shear thinning non-Newtonian fluidsFigshare - Mohadeseh Mozafari; Amirmohammad Sattari; Mohsen Mashhadi Keshtiban; Andreas Dietzel; Pedram Hanafizadeh (Results in Engineering, 2025)
This paper numerically investigates and detects the liquid-liquid two-phase flow patterns in a T-junction microchannel for shear-thinning non-Newtonian fluids to observe the effects of rheology, microchannel diameter, flow rate, and the surface tension on the two-phase flow patterns. The study employs water and three different shear-thinning aqueous solutions at different concentrations. The simulations were conducted using the conservative Level-set Method, and four main flow patterns of droplet flow, slug flow, jet flow, and parallel flow are observed, and the flow map is then identified. Weber and Reynolds numbers were then used in this study to predict the flow patterns. The results represent that fluid viscosity can shift the transition line in the flow map in a way that an increase in the viscosity improves the probability of forming the droplet flow pattern since growing viscous forces help the jet flow to separate and create the droplets. To investigate whether the different flow regimes can also be identified continuously in the experiment, the impedance pulse sensor principle was analyzed numerically. Unlike microscopic analysis, this technique allows online detection and provides feed-back regulation with which the flow regimes can be stabilized by regulating the inflows. The results show that by comparing two separate sensor zones, the change in the impedance signal characterizes different flow regimes, and the sizes of droplets or slugs can be recognized. This technique can therefore be used in the future to experimentally verify flow maps and to stabilize the two-phase flow patterns by feed-back regulation.